Design, construction and performance evaluation of a commercial ice-maker (2006)
The ice-maker (freezer) was designed, constructed and tested. The ice-making machine is to freeze 27kg of water in 9 different compartments in 12 hrs. The quantity of heat to be removed in order to achieve freezing is 12556.89 kJ and this is used to determine the refrigeration tonnage of the machine (0.124 ton). Polyurethane and Galvanized steel sheets have been selected for insulation and cabinet materials respectively due to their low thermal conductivities and high corrosion resistant properties. The performance tests show that the ice-maker is capable of producing 9 ice cubes (10 cm x 10 cm x 30 cm) in 12 hrs; while the economic analysis indicate that the project iseconomically viable. The cost of the ice-maker is N 51,650.00 and the investment payback is estimated to be 74 days with regular supply of electricity.